Data mining techniques and applications : an introduction - Du, Hongbo Hongbo Du (Australia: Cengage Learning, 2010)
This concise and approachable introduction to data mining selects a mixture of data mining techniques originating from statistics, machine learning and databases, and presents them in an algorithmic approach
Includes bibliography and index
Keywords: Data mining